2022
DOI: 10.3390/ijms23136976
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study of N2 Adsorption on Hydrogenated Y2C4H− and Dehydrogenated Y2C4− Cluster Anions at Room Temperature

Abstract: The adsorption of atmospheric dinitrogen (N2) on transition metal sites is an important topic in chemistry, which is regarded as the prerequisite for the activation of robust N≡N bonds in biological and industrial fields. Metal hydride bonds play an important part in the adsorption of N2, while the role of hydrogen has not been comprehensively studied. Herein, we report the N2 adsorption on the well-defined Y2C4H0,1− cluster anions under mild conditions by using mass spectrometry and density functional theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…[42,43] The findings of these studies on clusters may provide some molecular-level reaction mechanisms of N 2 activation on practical NRR catalysts. Particularly, clusters containing Y [44][45][46][47] or Co [48] and some metal carbide clusters, such as Y 2 C 4 À and Y 2 C 4 H À , [46] CoTaC 2 À , [48] V 3 C + , [49] V 3 C 4 À , [50] Ta 2 C 4 À , [51] PtC 4-6 À , [52] FeV 2 C 2 À , [53] FeTaC 2 À , [54] V 3-…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[42,43] The findings of these studies on clusters may provide some molecular-level reaction mechanisms of N 2 activation on practical NRR catalysts. Particularly, clusters containing Y [44][45][46][47] or Co [48] and some metal carbide clusters, such as Y 2 C 4 À and Y 2 C 4 H À , [46] CoTaC 2 À , [48] V 3 C + , [49] V 3 C 4 À , [50] Ta 2 C 4 À , [51] PtC 4-6 À , [52] FeV 2 C 2 À , [53] FeTaC 2 À , [54] V 3-…”
Section: Introductionmentioning
confidence: 99%
“…The findings of these studies on clusters may provide some molecular‐level reaction mechanisms of N 2 activation on practical NRR catalysts. Particularly, clusters containing Y [44–47] or Co [48] and some metal carbide clusters, such as Y 2 C 4 − and Y 2 C 4 H − , [46] CoTaC 2 − , [48] V 3 C + , [49] V 3 C 4 − , [50] Ta 2 C 4 − , [51] PtC 4‐6 − , [52] FeV 2 C 2 − , [53] FeTaC 2 − , [54] V 3‐ x Ta x C 4 − ( x =0–3), [55] were found to have high reactivity toward N 2 . This work aims to experimentally observe the reactions between Y−Co heteronuclear metal carbide cluster anions and N 2 at room temperature, and theoretically analyze the reaction mechanisms based on density functional theory (DFT) calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Gas-phase clusters usually contain metal atoms coupled with inorganic ligands, such as oxygen, boron, hydrogen, carbon, sulfur, and so on. 29,[32][33][34][35] For example, we recently reported that in NbB 3 O 2 À , the B 3 O 2 ligand and the single Nb center can form a dual active site to promote N 2 activation and transformation. 29 In the NbH 2 À /CO 2 /N 2 system, the NbN 2 À anion is formed by the reaction of NbH 2 À with N 2 , and the NRN triple bond is cleaved with the formation of the C-N bond in the reaction of NbN 2 À with CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the study of gas-phase reactions under isolated conditions with well-characterized chemical and molecular structures constitutes an alternative way to probe the intrinsic structure–reactivity relationship of N 2 activation by metal clusters. With continuous efforts from many research groups, to date, a variety of homo/heteronuclear metal clusters have been successfully identified to be capable of fully cleaving the NN triple bond, the metal centers of which include Ti 2 , Gd 2 , Ta 2 , , Ta 3 , Ta 4 , Ta 6 , FeTa, V 3 , , FeV 2 , Sc 2 , Nb, ,, etc., as summarized in Figure . Considering the high NN bond strength, the mechanistic focus of these studies was often to elucidate the NN cleavage pathway.…”
Section: Introductionmentioning
confidence: 99%